MATHEMATICAL MODELS FOR THE SIMULATION OF PUMPS SYSTEMS - Kastrevc, Mitja; Detiček, Edvard (Journal of Energy Technology, 2024)
This paper presents the influence of a mathematical model in the simulation of pumping systems; specifically, a model of an induction motor is presented; the paper also covers a comparison between commonly used mathematical models of AC motors.For verification of the simulated data, a practical pump system was tested.